Structural commonalities and deviations in the hierarchical organization of crossed-lamellar shells: A case study on the shell of the bivalve Glycymeris glycymeris. Issue 5 (11th March 2016) - Böhm, Corinna F.; Demmert, Benedikt; Harris, Joe; Fey, Tobias; Marin, Frédéric; Wolf, Stephan E.
Abstract: Abstract : The structural organization of the palliostracum—the dominant part of the shell which is formed by the mantle cells—of Glycymeris glycymeris (Linné 1758) is comprised of five hierarchical levels with pronounced structural commonalities and deviations from other crossed-lamellar shells. The hierarchical level known as second order lamellae, present within other crossed-lamellar shells, is absent highlighting a short-coming of the currently used nomenclature. On the mesoscale, secondary microtubules penetrate the palliostracum and serve as crack arrestors. Moreover, the growth lamellae follow bent trajectories possibly impacting crack propagation, crack deflection, and energy dissipation mechanisms whilst circumventing delamination. Finally, at least two structural elements are related to external circatidal and circaanular stimuli. This emphasizes that endogeneous rhythms may contribute and (co-)control the self-organization of a complex mineralized tissue and that it is insufficient to rely fully on a reductionistic approach when studying biomineralization.